2016
DOI: 10.1016/j.juro.2016.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and Clinical Predictors of Switching to Active Treatment among a Large, Ethnically Diverse Cohort of Men with Low Risk Prostate Cancer on Observational Management

Abstract: Purpose To determine the clinical and sociodemographic predictors of beginning an active treatment among an ethnically diverse population of men with low-risk prostate cancer initially on observational management. Materials and Methods We retrospectively studied men diagnosed with low-risk prostate cancer between 2004 and 2012 at Kaiser Permanente Northern California, who did not receive any treatment within the first year of diagnosis and had at least two years of follow-up. We used Cox proportional hazards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…[912] Additionally, studies suggest that men may not be adherent with monitoring protocols, particularly in obtaining surveillance biopsies. [13, 14] While AS may mitigate the harms of overdiagnosis, lack of adherence with surveillance monitoring could lead to more men progressing to advanced-stage, incurable disease.…”
Section: Introductionmentioning
confidence: 99%
“…[912] Additionally, studies suggest that men may not be adherent with monitoring protocols, particularly in obtaining surveillance biopsies. [13, 14] While AS may mitigate the harms of overdiagnosis, lack of adherence with surveillance monitoring could lead to more men progressing to advanced-stage, incurable disease.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to eligibility criteria, follow-up strategies, and thresholds for intervention also contributed to decision for radical treatment ( 41 ). Sociodemographic factors including race, age, education level and comorbidities have been found to be associated with AS discontinuation ( 42 - 44 ). Kelly et al ( 42 ) found that black men were more likely to switch to active treatment, which has been described in prior studies ( 44 ).…”
Section: Intervention Without Clinical Progressionmentioning
confidence: 99%
“…Sociodemographic factors including race, age, education level and comorbidities have been found to be associated with AS discontinuation ( 42 - 44 ). Kelly et al ( 42 ) found that black men were more likely to switch to active treatment, which has been described in prior studies ( 44 ). Additionally, the authors found black men were less likely to undergo serial re-biopsy perhaps explaining the higher rates of eventual treatment.…”
Section: Intervention Without Clinical Progressionmentioning
confidence: 99%
“…In one large retrospective analysis of 24.450 patients with low risk PCa suitable for AS, over half (55%) selected definitive treatment over AS ( 46 ). Kelly et al ( 47 ) found 27% of patients initially on AS opted for definitive treatment within 2.9 years of follow-up. Although practice patterns have shifted over the last decade towards more conservative treatments, the role of mpMRI in maintaining men on AS has not been explored.…”
Section: Evolving Role: Evaluating Active Surveillance Candidacymentioning
confidence: 99%